The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1017/gmb.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Microbial lactate utilisation and the stability of the gut microbiome

Abstract: The human large intestinal microbiota thrives on dietary carbohydrates that are converted to a range of fermentation products. Short-chain fatty acids (acetate, propionate and butyrate) are the dominant fermentation acids that accumulate to high concentrations in the colon and they have health-promoting effects on the host. Although many gut microbes can also produce lactate, it usually does not accumulate in the healthy gut lumen. This appears largely to be due to the presence of a relatively small number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 67 publications
0
51
0
Order By: Relevance
“…As illustrated in Figure 1 , butyrate is produced by a distinct group of gut bacteria via either the CoA-transferase or butyrate kinase pathways [ 23 , 24 , 25 ]. Butyrate can only be produced by a distinct group of gut microbes, including Faecalibacterium prausnitzii and Eubacterium rectale [ 26 ]. A number of studies have identified that butyrate-producing bacteria are depleted in the gut microbiota of patients with inflammatory bowel diseases (including Crohn’s disease and ulcerative colitis) and colorectal cancer compared to healthy people [ 21 , 27 ].…”
Section: Postbiotics and Human Gut Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…As illustrated in Figure 1 , butyrate is produced by a distinct group of gut bacteria via either the CoA-transferase or butyrate kinase pathways [ 23 , 24 , 25 ]. Butyrate can only be produced by a distinct group of gut microbes, including Faecalibacterium prausnitzii and Eubacterium rectale [ 26 ]. A number of studies have identified that butyrate-producing bacteria are depleted in the gut microbiota of patients with inflammatory bowel diseases (including Crohn’s disease and ulcerative colitis) and colorectal cancer compared to healthy people [ 21 , 27 ].…”
Section: Postbiotics and Human Gut Healthmentioning
confidence: 99%
“…Acetate is the most abundant SCFA in the gut reaching a molar ratio three times larger than butyrate and propionate [ 16 , 26 , 33 ]. Acetate is produced through the fermentation of dietary fibres by gut bacteria, including Ruminococcus spp., Prevotella spp., Bifidobacterium spp.…”
Section: Postbiotics and Human Gut Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Colonic CO2 is a fermentative subproduct of the bicarbonate/acid reaction performed by commensals such as Bifidobacteria and butyrate-producing Clostridial clusters(Heresbach et al, 1995;Rivière et al, 2016). Short-chain fatty acids (acetate, propionate and butyrate) are the dominant fermentation acids that accumulate to high concentrations in the colon(Louis et al, 2022). The extreme acid load associated with high colonic p CO2 is partially counteracted by the proximal colon epithelium's apical membrane, that provides a significant resistance towards CO2 diffusion and confers cellular protection(Endeward and Gros, 2005).The intestinal CO2 enters red blood cells and is converted to carbonic acid, which dissociates to hydrogen ion and bicarbonate.…”
mentioning
confidence: 99%